Effects of a 12-Week Modified German Volume Training Program on Muscle Strength and Hypertrophy-A Pilot Study - Daniel A. Hackett; Theban Amirthalingam; Lachlan Mitchell; Yorgi Mavros; Guy C. Wilson; Mark Halaki (MDPI AG, 2018)
This study investigated the effect of a 12-week modified German Volume Training intervention, or the 10 sets method, on muscle strength and hypertrophy. Twelve healthy males were randomly assigned to either a 5-SET or 10-SET group and performed 5 or 10 sets, respectively, of 10 repetitions at 60-80% one-repetition maximum (1RM). Muscle strength and body composition measures were taken at baseline, six weeks, and after 12 weeks of training. No significant changes in total, trunk, and arm lean mass were found within and between groups at any time point. There was no significant difference between groups for lean leg mass. However, a decrease in lean leg mass was observed within the 10-SET group between six and 12 weeks (p = 0.02). An increase in 1RM bench press was found within the 5-SET group at week 6 (p = 0.001) and 12 (p = 0.001) when compared to baseline, while no increases in 1RM leg press were observed at any time point within any group. No significant differences were found for 1RM bench press and leg press between groups. For 1RM bench press moderate effect sizes (ES) favored 5-SET and for 1RM leg press small ESs favored 10-SET. Findings suggest performing >5 sets per exercise does not promote greater gains in muscle strength and hypertrophy. Future research should aim to substantiate these preliminary findings in a larger cohort.